Blunted insula activation reflects increased risk and reward seeking as an interaction of testosterone administration and the MAOA polymorphism. Issue 9 (12th June 2017) - Wagels, Lisa; Votinov, Mikhail; Radke, Sina; Clemens, Benjamin; Montag, Christian; Jung, Sonja; Habel, Ute
Abstract: Testosterone, a male sex hormone, has been suggested to partly explain mixed findings in males and females when investigating behavioral tendencies associated with the MAOA polymorphism. Prior studies indicated that the MAOA polymorphism represents a vulnerability factor for financial risk‐taking and harm avoidance and that testosterone increases human risk‐taking. We therefore assumed an interactive influence of the MAOA polymorphism and testosterone application on decision making and corresponding neural correlates in a risk and reward context. Stratified for the MAOA polymorphism (S =short, L =long), 103 healthy males were assigned to a placebo or testosterone group (double blind, randomized) receiving a topical gel containing 50 mg testosterone. During a functional MRI scan, the participants performed a sequential decision making task. Our results indicate that testosterone and the MAOA polymorphism jointly influence sequential decision making. The MAOA‐S variant was associated with less automatic harm avoidance as reflected in response times on safe decisions. Moreover, after testosterone administration, MAOA‐S carriers were more risk‐taking. Overall activity in the anterior cingulate cortex, anterior insula and inferior frontal gyrus increased with growing risk for losses. In the anterior insula, testosterone administration mitigated this effect solely in MAOA‐S carriers. This might be a reflection of an improved coping during risk‐reward conflicts subsequently modulating risky decision making. While the molecular basis is not well defined so far, our results support the assumption of testosterone as a modulatory factor for previously reported sex differences of behavioral associations with the MAOA‐S variant. Hum Brain Mapp 38:4574–4593, 2017 . ©2017 Wiley Periodicals, Inc.